A trama faustiana do capital financeiro na captura da unidade de produção familiar - Silva, José Danilo Santana (2014)
With the end of Keynesianism as an economic model to overcome the crisis of overproduction that was established in the late 1970s, the mundialization of capital appears as a process of a new rate of accumulation. The international integration of markets was ensured through the liberalization and deregulation of national and automating the flow of capital markets. For this purpose, it was up to the central states take over and determine the course of neoliberal policy, removing institutional and economic barriers that could create hinders to the free flow of capital. In Brazil, the inclusion of financial capital in the field to give technical modernization during the military dictatorship. It was necessary to transform the field to meet the foreign trade of the production demand, increase productivity without changing the agrarian structure through technical integration between industry and agriculture. The integration of financial capital to agriculture comprises the strengthening of a rural credit system and mechanisms of fiscal and financial incentives from the state, intensification of interindustry relationships (with the fusion of agro-industrial capital in the private sector and the consolidation of multi-sectoral clusters) and transformation in the land market. Under the aegis of agribusiness, finance capital takes control of the development of the Brazilian field, so chasing the profit income from the land by state policies. In this sense, the challenge of our master's research is to analyze the spatial repercussions of insertion of finance capital in Sergipe field, analyze how this deed the land to extract directly or indirectly fractions of more value and land rent. . It is important to observe that the financial capital belongs to the field not only through direct financing, production and marketing of goods, the credit system presence permeates other dimensions of income of peasant production unit. Therefore, we analyzed the Territory of the Alto Sertão Sergipano with the objective to identify the forms and strategies of financial capital for profit, especially through the subordination of the family production unit to the accumulation process, analyzing the State's actions in apprehending dialectic of movement favoring the capital with that consists of indissociable and interconnected way your metabolic reproduction system.